2019
DOI: 10.1109/tit.2019.2927020
|View full text |Cite
|
Sign up to set email alerts
|

Probabilistic Existence Results for Parent-Identifying Schemes

Abstract: Parent-identifying schemes provide a way to identify causes from effects for some information systems such as digital fingerprinting and group testing. In this paper, we consider combinatorial structures for parent-identifying schemes. First, we establish an equivalent relationship between parent-identifying schemes and forbidden configurations. Based on this relationship, we derive probabilistic existence lower bounds for two related combinatorial structures, that is, t-parent-identifying set systems (t-IPPS)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…Recently, Gu, Cheng, Kabatiansky and Miao [22] showed that for fixed integers t ≥ 2, r ≥ 3, there exists a t-IPPS(r, m, n) with m = Ω(n r ⌊t 2 /4⌋+t ), which implies that for ⌊t 2 /4⌋ + t | r the upper bound in [23] is tight up to a constant factor. We slightly improve the lower bound of [22] for some pairs of r, t. Proposition 9 is proved by establishing a connection between IPPSs and sparse hypergraphs, as stated below. Note that a similar observation with different phrasing was obtained independently in [22].…”
Section: Parent-identifying Set Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Gu, Cheng, Kabatiansky and Miao [22] showed that for fixed integers t ≥ 2, r ≥ 3, there exists a t-IPPS(r, m, n) with m = Ω(n r ⌊t 2 /4⌋+t ), which implies that for ⌊t 2 /4⌋ + t | r the upper bound in [23] is tight up to a constant factor. We slightly improve the lower bound of [22] for some pairs of r, t. Proposition 9 is proved by establishing a connection between IPPSs and sparse hypergraphs, as stated below. Note that a similar observation with different phrasing was obtained independently in [22].…”
Section: Parent-identifying Set Systemsmentioning
confidence: 99%
“…We slightly improve the lower bound of [22] for some pairs of r, t. Proposition 9 is proved by establishing a connection between IPPSs and sparse hypergraphs, as stated below. Note that a similar observation with different phrasing was obtained independently in [22].…”
Section: Parent-identifying Set Systemsmentioning
confidence: 99%
“…In this paper we shall investigate the value I 2 (n, 4) for 2-IPPS(n, 4), especially, when n is sufficiently large. Notice that it is reasonable to consider large n and relatively small k. In fact, the dealer needs a large set of base keys to accommodate amounts of authorized users, however, each authorized user is usually assigned with a limited number of base keys which are used as the user's inputs to the decryption devices [6].…”
Section: Lemma 14 ([6]mentioning
confidence: 99%
“…Another known scheme, based on arbitrary (w, n)threshold SSS, was proposed in [25,7] and is known under the name of set systems with the identifiable parent property (IPP set systems). The most recent results can be found in [11,16,10,15,12]. The generalization of these two schemes was proposed in [9].…”
Section: Introductionmentioning
confidence: 99%